Chicoric acid attenuate a nonalcoholic steatohepatitis by inhibiting key regulators of lipid metabolism, fibrosis, oxidation, and inflammation in mice with methionine and choline deficiency - Kim, Myungsuk; Yoo, GyHye; Randy, Ahmad; Kim, Hyoung Seok; Nho, Chu Won (WILEY, 2017)
Scope: Nonalcoholic fatty liver diseases (NAFLD) range histopathologically from hepatic steatosis to steatohepatitis. Chicoric acid has beneficial effects on obesity and liver injury, but its effects on nonalcoholic steatohepatitis (NASH) have not yet been determined. This study examined the effects of Crepidiastrum denticulatum extract (CDE) and its active compound chicoric acid in a mouse model of NASH and fibrosis. Methods: CDE and chicoric acid were orally administrated to mice fed a methionine-and choline-deficient (MCD) diet. HepG2 and AML-12 cells in MCD medium were incubated with chicoric acid. MCD-fed mice developed the histopathological characteristics of human NASH, including altered regulation of lipid metabolism, inflammation, fibrosis, and oxidation-associated expression, along with augmented lipoperoxidation. Administration of CDE or chicoric acid to MCD-fed mice and HepG2 and AML-12 cells in MCD medium reduced oxidative stress by upregulating antioxidant enzymes and decreased inflammation by inhibiting proinflammatory cytokines and nuclear factor-kappa B activation. In addition, CDE or chicoric acid reduced fibrosis, apoptosis, and lipogenesis-related gene expression and increased AMP Kinase activation both in vivo and in vitro. Conclusions: CDE and chicoric acid may be effective in the treatment of NAFLD and NASH.
Keywords: FATTY LIVER-DISEASE; NF-KAPPA-B; EMERGING MOLECULAR TARGETS; INDUCED HEPATIC STEATOSIS; ACTIVATED PROTEIN-KINASE; IN-VITRO; INSULIN-RESISTANCE; SIGNALING PATHWAYS; CHLOROGENIC ACID; STELLATE CELLS